CASE MANAGEMENT FOR PEOPLE WITH STROKE: QUASI-EXPERIMENTAL STUDY - Pollyanna Bahls de Souza; Maria de Fátima Mantovani; Aida Maris Peres; Sonia Silva Marcon; Alexandra Bittencourt Madureira; Vania Gryczak Gevert (Cogitare Enfermagem, 2022)
Objective: to compare the effect of intervention by nurse-case manager on risk factors and blood pressure in post-stroke people.